Balanza Comercial Entre Miembros De La Alianza Pacifico 2012 2022 (2025)
Like all agreements, economic alliances or bilateral or multilateral free trade agreements between countries have a maturation process from the moment the idea is conceived by those interested, as is the case with the Pacific Alliance, a group of four countries, Mexico, Colombia, Peru and Chile, which among other aspects have in common that of sharing coasts on the Pacific Ocean and therefore the possibility of exploiting the markets of Southeast Asia and especially China.